Crystallization Behavior of Glycine Molecules with Electrolytic Dissociation on Charged Silica Gel Particles. Issue 6 (14th February 2018) - Deki, Yuto; Kadota, Kazunori; Onda, Saori; Tozuka, Yuichi; Shimosaka, Atsuko; Yoshida, Mikio; Shirakawa, Yoshiyuki
Abstract: The surface charge of metal oxides in the solution phase may be a driving force for crystallization. Composite particles were prepared using the principle of heterogeneous nucleation on a metal surface with varying charge density. The electrical properties of the silica gel particles in an electrolyte solution were controlled by the pH, and the zero charge point and charge density of the silica gel particles were determined by titration. The morphology of the glycine particles on the silica gel surface depended on the electrical properties of the silica gel particle, resulting in alteration of the glycine polymorph. Powder X‐ray diffraction showed that γ ‐glycine was present at low pH, and α ‐glycine, at high pH. The polymorphism arose from the abundance ratio of the solute ions and the solution structure. Abstract : To study the surface charge of metal oxides in solution as a driving force for crystallization, glycine/silica gel composite particles were prepared by heterogeneous nucleation. The glycine particle morphology on the silica gel surface depends on the electrical properties of the silica gel particle. The glycine polymorph varies with the abundance ratio of the solute ions and the solution structure.